Novel apigenin based small molecule that targets snake venom metalloproteases. - Venkatachalaiah Srinivasa; Mahalingam S Sundaram; Sebastian Anusha; Mahadevappa Hemshekhar; Siddaiah Chandra Nayaka; Kempaiah Kemparaju; Basappa; Kesturu S Girish; Kanchugarakoppal S Rangappa (PLoS ONE, 2014)
The classical antivenom therapy has appreciably reduced snakebite mortality rate and thus is the only savior drug available. Unfortunately, it considerably fails to shield the viper bite complications like hemorrhage, local tissue degradation and necrosis responsible for severe morbidity. Moreover, the therapy is also tagged with limitations including anaphylaxis, serum sickness and poor availability. Over the last decade, snake venom metalloproteases (SVMPs) are reported to be the primary component responsible for hemorrhage and tissue degradation at bitten site. Thus, antivenom inability to offset viper venom-induced local toxicity has been a basis for an insistent search for SVMP inhibitors. Here we report the inhibitory effect of compound 5d, an apigenin based molecule against SVMPs both in silico and in vivo. Several apigenin analogues are synthesized using multicomponent Ugi reactions. Among them, compound 5d effectively abrogated Echis carinatus (EC) venom-induced local hemorrhage, tissue necrosis and myotoxicity in a dose dependant fashion. The histopathological study further conferred effective inhibition of basement membrane degradation, and accumulation of inflammatory leucocytes at the site of EC venom inoculation. The compound also protected EC venom-induced fibrin and fibrinogen degradation. The molecular docking of compound 5d and bothropasin demonstrated the direct interaction of hydroxyl group of compound with Glu146 present in hydrophobic pocket of active site and does not chelate Zn2+. Hence, it is concluded that compound 5d could be a potent agent in viper bite management.